Formation of Cone-Shaped Inclusions and Line Defects on the Cz-Si Wafer Surface by the Helium Implantation and DC Nitrogen Plasma Treatment - Frantskevich, N. V.; Mazanik, A. V.; Frantskevich, A. V.; Koltunowicz, T.; Zukowski, P. (My University, 2011)
The general goal of this work is to investigate the defects formed on the surface of the Cz-Si wafers subjected to helium implantation, vacuum annealing and nitrogen plasma treatment. The performed scanning electron microscopy study has shown that in the general case two types of surface defects can be formed: cone-shaped inclusions with the base diameter of 0.2-2 mu m and the ratio of diameter to height of approximately 1:1, as well as crystallographically oriented line defects with the length equal to 0.2-2 mu m. The concentration of these defects depends on the conditions of implantation and plasma treatment.